偏遠地區公立國民中小學校績效獎金計畫之建構 School-based Performance Award Program for Public Schools in Taiwan's Remote Areas - 許添明 Tian-Ming Sheu; 林慧玲 Hui-Ling Lin (National Taiwan Normal University, 2009)
教育部透過各項補助計畫以改善偏遠地區國民中小學校學生學業成就低落的問題，甚至以離島、山僻加給吸引教師前往任教，但這些計畫對於提升該地區學生學習成就效果有限。本研究以偏遠地區校長、教師組成的焦點團體訪談與個別訪談，建構以學校為基礎的績效獎金計畫，不僅避免個人績效獎金制度引發的競爭，而且透過團隊合作方式有效提升學生學業成就。本計畫特點如下：採志願參加，教職員工績效獎金額度採同工同酬，學校也會獲得績效獎金，績效評核以學科績效為主，非學科績效為輔，並以平衡計分卡方式計算績效獎金。為了順利實施該計畫，本研究也提出配套措施：充足的經費來源，召開說明會並訂定試辦期，加強偏遠學校成員團隊合作與專業知能。 Students in Taiwan's remote areas have long been recognized for their poor performance in student achievement. To overcome this problem, government subsidies many programs including paying more to teachers who serve in these areas. However, student achievement in these areas has not seen much improvement. This research is to design a school-based performance award (SBPA) program for public schools in remote areas in the hope that this incentive will help to raise student achievement. After interviewing of one focus group and several individual teachers and principals in remote areas, we have developed this SBPA with the following features. First, it is voluntary to join the SBPA and the award applies to anyone who joins the program. Second, both individual teachers and schools are eligible for the performance award. Third, student achievement in five core academic subjects and four nonacademic factors are served as performance measures in the SBPA. Fourth, balanced scorecard is adopted as the bonus payout structure. Certain processes should be thought through for successful implementation of the SBPA.